2014
DOI: 10.1007/s13277-014-2756-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of autoantibodies to multiple tumor-associated antigens (TAAs) in the immunodiagnosis of breast cancer

Abstract: We aimed to evaluate the immunodiagnostic values of autoantibodies to a panel of six tumor-associated antigens (TAAs) in the detection of patients with breast cancer. This study determines whether a panel of multiple TAAs would enhance antibody detection and be a useful approach in breast cancer detection and diagnosis. The panel of multiple TAAs was composed of six TAAs including Imp1, p16, Koc, survivin, cyclin B1, and c-myc full-length recombinant proteins. Enzyme-linked immunosorbent assay (ELISA) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…After excluding 579 non‐English articles and 1318 duplicates, 4441 articles not relevant to the topic and 58 meeting the exclusion criteria were excluded. Ultimately, 84 articles were included . A total of 196 specific tumour‐associated autoantibodies (Table S1) were reported, of which 23 specific tumour‐associated autoantibodies (Table ) had been studied more than once.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding 579 non‐English articles and 1318 duplicates, 4441 articles not relevant to the topic and 58 meeting the exclusion criteria were excluded. Ultimately, 84 articles were included . A total of 196 specific tumour‐associated autoantibodies (Table S1) were reported, of which 23 specific tumour‐associated autoantibodies (Table ) had been studied more than once.…”
Section: Resultsmentioning
confidence: 99%
“…The 84 articles included participants from 27 countries (Table S1). The most studied populations were Chinese and American , followed by French , German and Italian . The earliest study was from 1982, and anti‐p53 antibody was the first tumour‐associated autoantibody to be reported in patients with BC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot serve as an indicator of early diagnosis of breast cancer. One of our previous studies showed other TAAs (such as Imp1, p16, Koc, survivin, cyclinB1 and c‐myc) had higher autoantibody response in breast cancer . However, diagnosis based on single tumour marker detection of either a TAA or an anti‐TAA antibody usually lacks sensitivity and specificity as noticed in most studies.…”
Section: Discussionmentioning
confidence: 96%
“…Diese Antikör-per richten sich beispielsweise gegen p53, CEA und RELT (receptor expressed in lymphoid tissues). Sie variieren je nach Tumorentität und aufgrund der Heterogenität der jeweiligen Tumorart auch teilweise innerhalb dieser [16][17][18][19][20]. Die bisherigen Arbeiten an diesem Themenkomplex können bei individuell ermittelten Grenzwerten weitgehend konstant hohe Spezifitäten berichten -bei teilweise sehr niedriger Sensitivität.…”
Section: Entwicklung Möglicher Tumormarkerunclassified